Design and synthesis of Ni2P/Co3V2O8 nanocomposite with enhanced electrochemical capacitive properties. (1st February 2016) - Hu, Yu-Mei; Liu, Mao-Cheng; Hu, Yu-Xia; Yang, Qing-Qing; Kong, Ling-Bin; Han, Wei; Li, Jia-Jia; Kang, Long
Graphical abstract: Ni2 P/Co3 V2 O8 nanocomposite with enhanced electrochemical behavior was designsd and synthesized by a facile chemical precipitation technique. The composite combines separately the pseudocapacitive advantages of both Co3 V2 O8 and Ni2 P, displays higher specific capacitance, excellent electrical conductivity, rate capability and cycling stability. Highlights: Ni2 P/Co3 V2 O8 nanocomposite was prepared through a facile chemical precipitation technique. The Ni2 P/Co3 V2 O8 nanocomposite displays higher electrical conductivity and excellent pseudocapacitive performance. AC//Ni2 P/Co3 V2 O8 supercapacitor is assembled and delivered high energy density and stable power characteristic. Abstract: In this paper, the Ni2 P/Co3 V2 O8 nanocomposite is synthesized by a facile chemical precipitation technique using Ni2 P (with high specific capacitance and electrical conductivity) and Co3 V2 O8 (with good rate capability and cycle stability) as precursor. The composite combines separately the advantages of the high specific capacitance of Ni2 P and the good rate capability as well as cycle stability of Co3 V2 O8, showing excellent pseudocapacitive properties. The specific capacitance of the Ni2 P/Co3 V2 O8 nanocomposite achieve 1002.5 F g −1 at a current density 1 A g −1 and maintain 605 F g −1 at 20 A g −1, 95% of its initial specific capacitance is retained after 3000 cycles. Also, an asymmetric supercapacitor is assembled, where Ni2 P/Co3 V2 O8 and activated carbon acted as the positive and negative electrodes, respectively. The maximum specific capacitance of 147.5 F g −1 and the specific energy of 40.2 Wh kg −1 are demonstrated at a cell voltage between 0 to 1.7 V, suggesting that the Ni2 P/Co3 V2 O8 nanocomposite is an ideal pseudocapacitive electrode material, which provided a new thinking for the potential application of hybrid electrode in energy-storage devices.